Literature Review: Digitalisasi Sebagai Strategi Pengembangan UMKM Di DKI Jakarta - Mustafa, Said; Aditiya, Variza; Hartutik, Dwi; Lastri, Novelma; Suprasman (LPPM STISIP IMAM BONJOL, 2024)
The development of MSME (Micro, Small, and Medium Enterprises) digitalization is a strategic step to increase competitiveness and economic growth in the digital era. By utilizing information technology and digital platforms, MSMEs can expand market reach, increase operational efficiency, and optimize business management. However, challenges such as limited access to technology, lack of digital literacy, and uneven infrastructure are still obstacles. Therefore, collaboration between the government, private sector, and the community is needed to provide training, access to funding, and infrastructure support to encourage MSME digital transformation in an inclusive and sustainable manner.